2020
DOI: 10.3390/min10090801
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Agglomeration of Fine Pyrite Particles Induced by Flotation Reagents

Abstract: Flotation reagents can change the surface properties of minerals, leading to differences in the interaction between mineral particles and affecting the mutual aggregation or dispersion of particles. In this work, we studied the role of activator copper sulfate, collector butyl xanthate and frother terpineol in adjusting the potential energy of pyrite particles from the perspective of the interfacial interaction. We evaluated the surface characteristics using contact angle analysis and zeta potential measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
4
2
0
Order By: Relevance
“…With increasing pH values, the absolute value of the zeta potential gradually increased. This is consistent with experimental data in the literature [33].…”
Section: Resultssupporting
confidence: 93%
“…With increasing pH values, the absolute value of the zeta potential gradually increased. This is consistent with experimental data in the literature [33].…”
Section: Resultssupporting
confidence: 93%
“…Hence, it is expected that the properties of the CNF surface will be affected by the added FeN@GnP powder. Cheng et al and Lu et al reported that hydrophobic surface properties induce high agglomeration due to the strong hydrophobic interaction between particles [39,40]. Therefore, compared to the hydrophilic FeN@GnP nanofiber support, the hydrophobic CNF support can enhance the aggregation of Co3O4 nanoparticles loaded on the surface of the nanofiber support, consistent with the SEM results.…”
Section: Resultssupporting
confidence: 82%
“…Hence, it is expected that the properties of the CNF surface will be affected by the added FeN@GnP powder. Cheng et al and Lu et al reported that hydrophobic surface properties induce high agglomeration due to the strong hydrophobic interaction between particles [31,32]. Therefore, compared to the hydrophilic FeN@GnP nanofiber support, the hydrophobic CNF support can enhance the aggregation of Co3O4 nanoparticles loaded on the surface of the nanofiber support, consistent with the SEM results.…”
Section: Resultssupporting
confidence: 82%